2023
DOI: 10.3389/fsurg.2023.1111024
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the paravertebral muscle in adult degenerative scoliosis with PI-LL match or mismatch and risk factors for PI-LL mismatch

Abstract: ObjectivePelvic incidence (PI) minus the lumbar lordosis (LL) angle (PI-LL) correlates with function and disability. It is associated with paravertebral muscle (PVM) degeneration and is a valuable tool for surgical planning of adult degenerative scoliosis (ADS). This study aims to explore the characteristics of PVM in ADS with PI-LL match or mismatch and to identify the risk factors for PI-LL mismatch.MethodsA total of 67 patients with ADS were divided into PI-LL match and mismatch groups. The visual analog sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…However, there was no correlation between the mean CSA and quality of life scores in the DLS group. We found that the degree of MF asymmetry in the DLS group correlated with a higher ODI and lower SF-36 RF, BP, GH, and PCS scores, consistent with previous studies' results [25,26].…”
Section: Discussionsupporting
confidence: 92%
“…However, there was no correlation between the mean CSA and quality of life scores in the DLS group. We found that the degree of MF asymmetry in the DLS group correlated with a higher ODI and lower SF-36 RF, BP, GH, and PCS scores, consistent with previous studies' results [25,26].…”
Section: Discussionsupporting
confidence: 92%
“…Studies have shown that [10,11] , changes in the structure and function of paraspinal muscles are often caused by fat infiltration and atrophy. The degree of fat infiltration in paraspinal muscles is often higher than that in lower extremity muscles, and the degree of fat infiltration in lumbar segments is often higher than that in cervical and thoracic segments.…”
Section: The Anatomical and Physiological Characteristics Of Paraspin...mentioning
confidence: 99%
“…In a different study by Guo et al [ 44 ], the characteristics of paravertebral muscles (PVMs) in ASD patients were studied with regard to pelvic incidence minus lumbar lordosis (PI–LL) match or mismatch. Out of 67 ASD patients, the PVM on the concave side was found to be larger than on the convex side in both PI–LL match and mismatch groups.…”
Section: Bone Quality and Sarcopenia: Their Role In Pjk/pjf After Asd...mentioning
confidence: 99%
“…In patients with osteoporosis or other conditions affecting bone health, it’s crucial to address this as part of the revision strategy. This could involve medical management such as teriparatide and bisphosphonate to improve bone density or the use of bone grafts or bone morphogenetic proteins to enhance fusion [ 27 , 44 , 63 ].…”
Section: Treatment Of Pjfmentioning
confidence: 99%